Functional Characterisation of GmGASA1-like Gene in Glycine max (L.) Merr.: Overexpression Promotes Growth, Development and Stress Responses - Mohamed A. S. Khalifa; Qi Zhang; Yeyao Du; Nooral Amin; Baozhu Dong; Piwu Wang (Life)
The presence of Gibberellic Acid-Stimulated Arabidopsis, GASA, gene family has been reported in many important plants, playing roles in various aspects of plant biology but little has been uncovered in soybeans. Soybean is one of the major plants providing nutrition for humans and livestock globally. In this study, we overexpressed a novel GASA gene (GmGASA1-like) in Glycine max and conducted bioinformatic analyses, evaluated the T2 transgenic line in an open field, and applied major stressors along with the growth promoter GA3 to investigate the potential functions of the GmGASA1-like gene. The results of bioinformatics implied that the GmGASA1-like gene is regulated by GA3, and its protein has the potential to influence key processes of plant growth and development. The transgenic plants (JN74-OE) were significantly taller and had a larger canopy in the field trial at the R1-growth stage and demonstrated superiority in some seed quantity and quality traits after harvesting. Under abiotic stresses (including cold, heat, and drought) and spraying of GA3, the level of GmGASA1-like gene expression in JN74-OE exceeded the levels measured before the treatments. Notably, the highest expression level was observed during the drought stress treatment. Photosynthesis pigments levels in both the overexpressed lines and the control group showed no significant differences. In summary, this study sheds light on the multifaceted roles of the GmGASA1-like gene, impacting soybean plant architecture, seed traits, and stress responses. Ultimately, this research paves the way for a more productive and sustainable soybean industry.